Replication Data for "Can Transfers and Complementary Nutrition Programming Reduce Intimate Partner Violence Four Years Post-program? Experimental Evidence From Bangladesh" - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
This is a replication data for the tables presented in the article, "Can transfers and complementary nutrition programming reduce intimate partner violence four years post-program? Experimental evidence from Bangladesh.” A detailed description of each variable in this dataset is included in this article. The sampling procedure employed and the raw data are also described in the article.